Screening of Charge Carrier Migration in the MgSc2Se4 Spinel Structure - Dillenz, Manuel; Sotoudeh, Mohsen; Euchner, Holger; Groß, Axel (Frontiers in Energy Research, 2020)
Periodic density functional theory calculations have been performed to study the migration of various charge carriers in spinel type MgSc2Se4. This compound exhibits low barriers for Mg ion diffusion, making it a potential candidate for solid electrolytes in Mg-ion batteries. In order to elucidate the decisive factors for the ion mobility in spinel-type phases, the diffusion barriers of other mono- and multivalent ions (Li+, Na+, K+, Cs+, Zn2, Ca2+, and Al3+) in the MgSc2Se4 framework have been determined as well. This allows for disentangling structural and chemical factors, showing that the ion mobility is not solely governed by size and charge of the diffusing ions. Finally, our results suggest that charge redistribution and rehybridization caused by the migration of the multivalent ions increase the resulting migration barriers.